Inserção do ciclo do tório e combustíveis reprocessados em reatores de água pressurizada no sistema energético nacional - Fidéllis Bitencourt Gonzaga Louzada e Estanislau (2023)
In response to the threat of global warming and climate change, the energy systems are changing. Nuclear energy is increasingly becoming an important option in the global energy matrix due to its low carbon characteristics and alternative fuel cycles could contribute to reducing the use of natural resources, managing waste and reducing greenhouse gas emissions. Given the context, this research proposes to evaluate and compare the use of alternative nuclear fuel cycles in pressurized water reactors based on the Brazilian nuclear energy system through indicators that simultaneously evaluate the trade-offs between aspects of natural resources consumption, fuel cycle performance and fuel costs. The evaluation of the fuel cycles is done using the MESSAGE model and the comparison between them is performed through a multicriteria analysis using the KIND-ET tool to determine the best scenarios. Assessment results show consumption of natural resources, accumulation or use of spent fuel, requirements of processes, nuclear waste, greenhouse gas emissions and costs of nuclear fuels. Reprocessed fuels tend to have fewer needs for extracting natural resources, lower amounts of spent fuel and waste generated with characteristics that make them more interesting to manage, in addition to lower greenhouse gas emissions. Open fuel cycles, on the other hand, have lower costs, ensuring greater economic viability. Within the adopted assumptions, the mixed oxide fuel, MOX, appears as the most promising. On the other hand, the sensitivity analysis carried out to capture the uncertainties shows that if costs have an importance greater than 55% for the decisions on the choice of the fuel cycle, the conventional fuel UOX appears as the most advantageous. Transuranic fuels have intermediate highlights and may still be options depending on the decision-makers intentions.